Prevalence of vulvovaginal candidiasis in females in the reproductive age group - Salvi, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vulvovaginal candidiasis (VVC) is a common infection among reproductive age group females. The objective of present study is to determine the prevalence of vulvovaginal candidiasis, its distribution and association of risk factors among reproductive age group females, attending the outpatient department of obstetrics and gynaecology of our Prime Medical Centre, Sharjah attached with Prime Hospital, Dubai, United Arab Emirates (UAE). Methods: It was cross-sectional descriptive study over a period of six months. Patients who came to our outpatient department with complains of vaginal discharge and itching in reproductive age group were included in this study. Patients characteristics i.e. age, parity, risk factors like diabetes, pregnancy, use of oral contraceptive pills (OCPills) and intrauterine contraceptive device (IUCD) were noted. High vaginal swabs (HVS) were collected and sent for culture. Candida positive cases were noted, and results were analyzed. Results: A total of 224 high vaginal swabs were collected. Prevalence of vulvovaginal candidiasis was found to be 31.6%. It was found more in 26-30 years age group and multiparous women. Previous history of candidiasis and diabetes were the commonest risk factors. Frequency of C. albicans was more (76.05%) than non-albicans candida (23.94%). Conclusions: Present study concluded that vulvovaginal candidiasis is more prevalent in reproductive age group females, therefore a routine high vaginal swab culture must be performed in every woman presenting with vaginal discharge and itching for correct diagnosis. Women should be educated on clinical symptoms.